The relationship between managerial ownership and firm performance in high R&D firms - Cui, Huimin; Mak, Y.T. (Journal of Corporate Finance, 2002)
Several studies have examined the relationship between managerial ownership and firm performance/value (e.g., [Journal of Financial Economics 20 (1988) 293; Journal of Financial Economics 27 (1990) 595; Journal of Corporate Finance 5 (1999) 79]). Using different samples, these studies provide general support for the argument that increases in managerial ownership create countervailing interest alignment and entrenchment effects, leading to a nonlinear relationship between managerial ownership and firm performance. However, the actual form of this nonlinear relationship differs across the studies. The present paper examines the relationship between managerial ownership and performance for high R&D firms that are listed on the NYSE, AMEX and NASDAQ. We find that Tobin's Q initially declines with managerial ownership, then increases, then declines again and, finally, increases again—a W-shaped relationship. The findings from our study point to the importance of industry effects in the relationship between managerial ownership and firm performance.